2013
DOI: 10.1002/hyp.9875
|View full text |Cite
|
Sign up to set email alerts
|

Fire decreases near-surface hydraulic conductivity and macropore flow in blanket peat

Abstract: Many peatlands have been subjected to wildfire or prescribed burning but it is not 22 known how these fires influence near-surface hydrological processes. Macropores are 23 important flowpaths in the upper layers of blanket peat and were investigated through 24 the use of tension disk infiltrometers, which also provide data on saturated hydraulic 25 conductivity. Measurements were performed on unburnt peat (U), where prescribed 26 burning had taken place 2 years (B2), four years (B4) and >15 (B15+) years prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 50 publications
3
71
0
3
Order By: Relevance
“…On the other hand, the bulk densitywater retention plots presented by Thompson and Waddington (2013) for soil water pressures of -100mb flatten out considerably for bulk densities >0.17 g cm-3 and so the effects on water retention, at -100mb, of enhanced bulk density beyond the range we tested may not be substantially greater in the field for fire affected sites. The normal bulk density treatment was similar to bulk densities measured by Holden et al (2014) on unburned plots. As water was supplied from below throughout the experiment, water intercepted from precipitation was not accounted for, but past work has shown that dependence on precipitation can increase susceptibility to drought and reduce carbon uptake in Sphagnum (Nijp et al 2014).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…On the other hand, the bulk densitywater retention plots presented by Thompson and Waddington (2013) for soil water pressures of -100mb flatten out considerably for bulk densities >0.17 g cm-3 and so the effects on water retention, at -100mb, of enhanced bulk density beyond the range we tested may not be substantially greater in the field for fire affected sites. The normal bulk density treatment was similar to bulk densities measured by Holden et al (2014) on unburned plots. As water was supplied from below throughout the experiment, water intercepted from precipitation was not accounted for, but past work has shown that dependence on precipitation can increase susceptibility to drought and reduce carbon uptake in Sphagnum (Nijp et al 2014).…”
Section: Discussionsupporting
confidence: 70%
“…The fact that C. introflexus was unaffected reflects the species' lower Ellenberg indicator value for moisture (Table 1) and could indicate a risk of a shift to species which can tolerate lower water availability at high bulk density. Holden et al (2014) found that peat bulk densities decreased with time since burning, so leaving sites unburned for longer may create more favourable conditions for Sphagnum establishment. However, the high bulk density treatment in this experiment was actually lower than many of the bulk densities measured on burned plots by Holden et al (2014), suggesting that greater limitations to Sphagnum establishment may occur in the field.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Segundo , em solos onde a matéria orgânica é responsável pela agregação, a combustão contribui para a perda de estabilidade dos agregados e à libertação de partículas finas provenientes quer dos agregados quer das cinzas (Zavala et al, 2009). Este efeito causa a colmatação dos poros, principalmente na superfície do solo, o que contribui para a diminuição da capacidade de infiltração da água (Holden et al, 2014 Dada a diversidade dos graus de severidade que podem ocorrer num incêndio florestal, os resultados sugerem que os parâmetros associados à condutividade hidráulica têm um padrão heterogéneo no pós-incêndio, ou seja, existem distintos mosaicos de zonas de infiltração e de formação ou transmissão da escorrência (cawson et al, 2013;Keesstra et al, 2014). Este facto é relevante na altura de projetar planos de atuação e recuperação de solos queimados (Williams et al, 2015), onde um estudo detalhado poderá permitir a identificação de áreas de maior risco de erosão e a aplicação de medidas corretivas à microescala.…”
Section: Fig 6 -Cumulative Infiltration I In Function Of Time T unclassified